Peranan Badan Perencanaan Pembangunan Daerah pada Pembangunan Infrastruktur di Kabupaten Aceh Barat - Dewi, Melati; Zakia, Zakia (University of Muhammadiyah Aceh, 2022)
The Regional Development Planning Agency (BAPPEDA) of West Aceh Regency plays an active role as a coordinating planner, and controller of implementation as well as researcher and development of regional development. In planning, BAPPEDA coordinates so that regional heads can carry out all tasks and activities in order to achieve harmony, integration and harmony between all agencies, including agencies and regional offices, in order to achieve maximum use and effective results. In planning an infrastructure development is the main task of infrastructure and regional development This study aims to determine the roIe of the RegionaI DeveIopment PIanning Agency (BAPPEDA) in West Aceh district infrastructure development. This study uses a qualitative method, presenting in the process of analyzing information obtained from respondents and informants. Questionnaires, field notes and other official documents are sources of data collected directly at the Regional Development Planning Agency (BAPPEDA) in West Aceh District, while the informants in this study are functional officials and staff in the Infrastructure and Regional Development section (IPW) in Bappeda Aceh Barat District, and the*data collection method was a questionnaire in which 32 respondents were asked a series of questions or written statements to answer. The resuIts of this study can be concluded that the role of the Regional Development Planning Agency(BAPPEDA) in infrastructure development in West Aceh District is a task in the field of Infrastructure and Regional Development, as coordination and synchronization of regional development planning in the field of Infrastructure and Regional Development. And the Regional Development;Planning Agency (BAPPEDA) as a planning agency in the region as a support for government affairs in the field of planning and supporting government affairs in the field of research and development functions more as coordinator of management of infrastructure development both from government agencies and with the private sector/community.